The Implementation and Challenges Impact of E-Learning Among Asnaf Students in Perlis: Analyzing using SPSS AMOS - Wan Mustafa, Wan Azani; Che Lah, Noor Hidayah; Adnan, Ernie; Hanafi, Abdul Ghafur; Wan Muhamad, Wan Zuki Azman; Asni, Fathullah (Journal of Advanced Research Design, 2025)
The rapid expansion of e-learning in Malaysia, accelerated by the COVID-19 pandemic and national education policies, has highlighted significant disparities in digital access among marginalized communities, particularly the Asnaf students in Perlis. Despite national initiatives like CERDIK improving device accessibility, systemic challenges such as poor internet connectivity, limited digital literacy, and socio-economic constraints continue to hinder effective e-learning adoption. This study investigates the implementation and challenges of digital learning among Asnaf students, employing a quantitative survey of 105 Form 3 and Form 4 students from three secondary schools in Perlis. Data were collected through a structured questionnaire assessing awareness, engagement, and obstacles related to e-learning. Statistical analyses, including Confirmatory Factor Analysis (CFA), Composite Reliability (CR), and Discriminant Validity, were conducted using Statistical Package for the Social Sciences (SPSS), Analysis of Moment Structures (AMOS) (IBM SPSS AMOS) to ensure data reliability and construct validity. Results indicate that while 91% of students have access to digital devices, 71% struggle with unstable internet, 72% face technical difficulties, and 59% lack conducive study environments. CR (CR larger than or equivalent 0.70) confirmed internal consistency, yet engagement’s Average Variance Extracted (AVE) (0.38) fell below the threshold, signaling measurement limitations. This low AVE indicates weak convergent validity, suggesting that the engagement construct may not robustly capture students’ actual participation in e-learning. This study contributes to the discourse on digital equity by advocating for inclusive strategies that ensure sustainable and meaningful e-learning adoption among underprivileged students in Malaysia.